Association of ventricular extrasystoles and ventricular tachycardia with idioventricular rhythm. Issue 5 (May 1976) - Talbot, S; Greaves, M
Abstract : Patients with acute myocardial infarction were monitored for ventricular arrhythmias in the first 48 hours. Idioventricular rhythm (rate less than 100/minute) occurred in 35 out of 224 patients (15.6%) during the first day and in 13 out of 192 patients not receiving treatment on the second day (6.8%). This arrhythmia was frequently preceded by late ventricular extrasystoles, which often showed variation of their coupling intervals to the preceding QRS. Double ventricular extrasystoles separated by larger than or equal to 600 ms were also precursors of idioventricular rhythm. Idioventricular rhythm at times could be described as an escape rhythm, but on other occasions it was undoubtedly an accelerated rhythm. Spontaneous changes in the idioventricular cycle length were frequent on single one-minute electrocardiographic recordings. The rate of the dominant rhythm in patients with episodes of idioventricular rhythm was significantly slower than the heart rate of patients without this arrhythmia. Idioventricular rhythm was more frequent in patients with inferior infarction. Idioventricular rhythm sometimes preceded ventricular tachycardia but there was only a significant association between ventricular tachycardia and idioventricular rhythms with rates of over 75/minute. Irregular idioventricular rhythm frequently accelerated to ventricular tachycardia. It is suggested that the term benign idioventricular rhythm be reserved for those rhythms below 75/minute, and that the term rapid idioventricular rhythm should be used for rhythms between 75 and 120/minute. The rate of idioventricular rhythm is related to the probability of development of life-threatening ventricular arrhythmias during the first 48 hours after myocardial infarction.